Medullary Carcinoma of the Gastrointestinal Tract: Report on Two Cases with Immunohistochemical and Molecular Features - Cristina Colarossi; Marzia Mare; Giorgio La Greca; Marco De Zuanni; Lorenzo Colarossi; Eleonora Aiello; Eliana Piombino; Lorenzo Memeo (Diagnostics, 2021)
Medullary carcinoma of the colon is a rare histological variant characterized by a poorly differentiated morphology, an aberrant immunophenotype, and microsatellite instability. Despite the lack of glandular differentiation, medullary carcinoma is reported to have a good prognosis. It is typically located in the right colon and frequently affects older women. Due to its clinical, histological, biological, and genetic peculiarity, medullary carcinoma requires an accurate diagnosis and the awareness of this diagnostic possibility. We describe the morphological, immunohistochemical, and molecular findings of two interesting cases, the first one in the right colon of a patient and the second one in the terminal ileum of a patient with Crohn’s disease. Deeper knowledge of all the biological and clinical features will allow appropriate and specific treatment of this tumor in the future.